Pseudo Double Bubble: Jejunal Duplication Mimicking Duodenal Atresia on Prenatal Ultrasound - David Schwartzberg; Sathyaprasad C Burjonrappa (EL-Med-Pub, 2013)
Prenatal ultrasound showing a "double bubble" is considered to be pathognomonic of duodenal atresia. We recently encountered an infant with prenatal findings suggestive of duodenal atresia with a normal karyotype who actually had a jejunal duplication cyst on exploration. A finding of an antenatal "double bubble" should lead to a thorough evaluation of the gastrointestinal tract and appropriate prenatal/neonatal testing and management as many cystic lesions within the abdomen can present with this prenatal finding.